Meta-analysis as an emerging trend to scrutinize the effectiveness of L2 pragmatics instruction - Shakki, Farzaneh (Frontiers in Psychology, 2022)
How efficient is instruction in pragmatics? The concern for answering this question has been taken into account through meta-analyses. Considering the plethora of studies conducted in pragmatic instruction, it is still challenging for the researchers to keep up with the literature, so aggregating the findings across multiple studies and comparing their results systematically in various dimensions can be pivotal to make sure whether this kind of research is effective or not. This review paper delineates the previous meta-analyses and reviews conducted in the field of instructed second language pragmatics to unravel the importance of conducting meta-analyses and to recommend some suggestions and pedagogical implications for further studies.